Shaping Non-Linear Soundscapes : Creative and Technical Approaches for Game Audio Mixing - Saarinen, Mikko (Taideyliopiston Sibelius-Akatemia, 2025)
This thesis examines the audio mixing process for video games and is aimed at anyone interested in the field of interactive audio. The research focuses on the creation of a mix that aligns with a game’s core design and artistic vision while meeting today’s technical standards and requirements. Written from a sound designer’s perspective, the thesis explores workflows, tools, and techniques for mixing in non-linear media, offering a practical and holistic lens that considers the technical, artistic, and collaborative aspects of interactive audio. This study examines how a well-crafted mix enhances gameplay clarity, immersion, and emotional impact, ensuring that players receive essential auditory feedback while experiencing a compelling soundscape. A significant focus is placed on practical implementation, including the role of audio middleware, real-time mix adjustments, and technologies such as object-based audio and 3D spatialization. Case studies of existing games, along with reflections on personal industry experience, provide real-world examples of interactive mixing solutions. By bridging academic research and industry practice, this thesis serves as both an educational resource and a reference for professionals, offering insights into the evolving landscape of game audio mixing in modern interactive media.
Keywords: game audio; sound design; Wwise (Wave Works Interactive Sound Engine); FMOD; computer games; mixing (sound); audio design; game music; middleware; interactive art; fi=musiikkiteknologia|sv=musikteknologi|en=Music Technology|